Is Immediate Postoperative Radiograph Necessary Following Robotic-Assisted Total Knee Arthroplasty? - Giordano, Joshua R.; Bartlett, Lucas; Huyke, Fernando; Sadh, Puru; Thompson, Kiara; Ajah, Obinnah; Danoff, Jonathan (The Journal of Knee Surgery, 2024)
The necessity of immediate postoperative radiographs following total knee arthroplasty (TKA) has long been debated. With the increasing use of robotic-assisted TKA (RTKA), and thus more precise implant placement, the need for immediate postoperative radiographs to determine implant positioning may be unnecessary. We sought to evaluate implant position on the immediate postoperative radiographs following RTKA to determine their necessity. A retrospective review of 150 RTKAs was performed. The posterior slopes for all TKAs were recorded based on the preoperative three-dimensional template. Additionally, two independent trained researchers (J.G./L.B.) each measured the posterior slope of the postoperative day 0 (POD0) radiograph and postoperative week 2 radiograph. The difference in posterior slope measurement between template and POD0, between template and postoperative week 2, and between POD0 and postoperative week 2 was calculated. Of the 150 TKAs performed, there were no periprosthetic fractures found on the POD0 radiograph. The mean difference between the templated posterior slope and measured posterior slope on POD0 was 0.04 degrees (standard deviation [SD], 1.01; p = 0.615). There was a weak correlation between the two values (rs [95% confidence interval (CI)], 0.38 [0.21, 0.53]). When comparing the template to the postoperative week 2 radiographs, there was a mean difference of 0.02 degrees (SD, 0.48; p = 0.556).  However, a moderate to strong correlation was noted (rs [95% CI], 0.71 [0.61, 0.79]). Comparison of the mean posterior slope from POD0 radiograph to that of postoperative week 2 radiograph showed a mean difference of 0.06 degrees (SD, 1.0; p = 0.427). A weak correlation was found between these two values (rs [95% CI], 0.43 [0.26, 0.56]). Given the accuracy and precision of RTKA, along with the ability to decrease cost and radiation, immediate postoperative radiograph may be unnecessary, when pertaining to the uncomplicated RTKA. However, if there is concern for intraoperative fracture, long stems placed in a revision arthroplasty, or other intraoperative complications, then postoperative radiographs are encouraged.
Keywords: total knee arthroplasty; robotics; radiograph; postoperative